Ambient condition retention of band-gap tuning in MAPbI3 induced by high pressure quenching. Issue 94 (8th November 2018) - Bonomi, Sara; Tredici, Ilenia; Albini, Benedetta; Galinetto, Pietro; Rizzo, Aurora; Listorti, Andrea; Tamburini, Umberto Anselmi; Malavasi, Lorenzo
Abstract : In the present work, we show a successful approach to achieve stable structural and optical changes induced by pressure on bulk amounts of MAPI after pressure release. Abstract : In the present work, we show a successful approach to achieve stable structural and optical changes induced by pressure on bulk amounts of MAPI after pressure release. Such effects on the optical properties resemble those achieved in situ ( e.g., in diamond anvil cells) but are retained and stabilized under ambient conditions thanks to a partial quenching of the high-pressure state.